2001
DOI: 10.1016/s0140-6736(00)04820-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breastfeeding on mortality among HIV-1 infected women: a randomised trial

Abstract: Our findings suggest that breastfeeding by HIV-1 infected women might result in adverse outcomes for both mother and infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
2
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(64 citation statements)
references
References 21 publications
2
53
2
6
Order By: Relevance
“…A randomized trial conducted in Kenya compared breastfeeding to formula feed--ing and reported there was an increased risk of maternal death among women who breastfed their infants. 10 However, the number of events in this second--ary analysis was small (24 deaths). Two subsequent observational studies from South Africa and the United Republic of Tanzania found no association between breastfeeding and maternal mortality among women infected with HIV.…”
mentioning
confidence: 83%
“…A randomized trial conducted in Kenya compared breastfeeding to formula feed--ing and reported there was an increased risk of maternal death among women who breastfed their infants. 10 However, the number of events in this second--ary analysis was small (24 deaths). Two subsequent observational studies from South Africa and the United Republic of Tanzania found no association between breastfeeding and maternal mortality among women infected with HIV.…”
mentioning
confidence: 83%
“…6,7 Infant factors that predict rapid disease progression include early acquisition of HIV, high viral load, early CD4 depletion and early onset of HIV-related symptoms such as growth delay, neurodevelopmental delay, hepatomegaly, splenomegaly and lymphadenopathy. [4][5][6][8][9][10][11][12] In the absence of HIV-1 infection, breast milk is known to protect against infectious disease and mortality in infancy through provision of passive immunity and nutrition to the infant.…”
Section: Introductionmentioning
confidence: 99%
“…Following this landmark study, different ART regimens have demonstrated variable impact in the reduction of HIV-1 vertical transmission rates (Dabis et al 1999, Guay et al 1999, Shaffer et al 1999, Wiktor et al 1999, PST 2002, Lallemant et al 2004, Read et al 2007). In addition to ART, other interventions have contributed to the reduction of HIV-1 vertical transmission, such as elective cesarean section (C-section) (IPHIVG 1999, EMDC 1999, vaginal cleaning during the intrapartum period (Taha et al 1997), vitamin A supplementation (Semba 1997), and avoidance of breastfeeding (Nduati et al 2001, RoUsseau et al 2004.…”
mentioning
confidence: 99%